Cold Surge Effect on Vertical Profile Atmosphere over Meteorological Station of Ranai Natuna: Case Study Asian Winter Monsoon 2019/2020 - Haryanto, Yosafat Donni; Prasetyo, Suwignyo; Hidayat, Ulil; Kurniawan, Wahyu; Riama, Nelly Florida (Universitas Negeri Surabaya, 2023)
During the Asian Winter season, which spans from November to February, the phenomenon of cold surge often occurs, leading to increased convective activity over the western Indonesian Maritime Continent. The location of Natuna Island, situated in the southern part of the South China Sea, is of particular importance for studying cold surges due to their propagation over this area. In this study, the vertical structure of the atmosphere was analyzed using radiosonde observation data collected at the Meteorological Station of Ranai Natuna. The analysis focused on physical parameters such as air temperature and relative humidity, atmospheric kinematics including wind direction and speed, as well as atmospheric thermodynamic parameters such as Lifting Condensation Level (LCL), Level of Free Convection (LFC), Equilibrium Level (EL), Convective Available Potential Energy (CAPE), and Convective Inhibition (CIN). The results indicate that during the passage of a cold surge, air temperature (T) tends to be higher in the lower troposphere, including at the surface, but lower in the middle and upper troposphere. Relative humidity (RH) also tends to be higher during cold surges, with a significant increase in the middle and upper troposphere. In the lower troposphere, the wind direction shifts from east to northeast at a higher speed compared to when a cold surge is absent. Furthermore, the LCL and LFC heights are elevated during the presence of a cold surge, while the EL height shows an insignificant decrease. It is worth noting that intense rainfall occurs, particularly when the cold surge is more pronounced, even though the values of CAPE and CIN do not change significantly.